Water plays - Aliaa El-Dardiry; Ahmed Ali Ahmed ElKhateeb; Ahmed El Antably (Studies in Digital Heritage)
This paper proposes a serious game that explores and digitally reconstructs the soundscape of the relocated Ottoman Sabīl (water dispensary) wa-Kuttāb (Quran elementary school) of Ismāʿīl al-Maghlawī, in historic Cairo, dated to 1657 CE. The sabīl was relocated in 1939 from its original location in Khān al-Khalīlī Street. It used to have an underground cistern, filled yearly with pure water from the Nile River, and provided water to passersby from its water dispensary room's window. The authors employed acoustic surveys to collect the impulse responses (IRs) in this sabīl toward developing an auralization using Odeon software. The auralized files were then deployed as a game using the Unity game engine, where players can identify the sabīl's architecture, soundscape, and spatial transformation over time. The game reveals the reverberating sounds of the sabīl's water path and, in the process, highlights the importance of acoustic documentation in the reconstruction of heritage buildings.